Lesya Ukrainka’s lyrical works рeculiarities of translation by M. Komissarova (concerning the poetic echo of fate in Lesya Ukrainka’s lyrics) - Шепель, Юрій Олександрович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article is devoted to the study one of the topics that are topical in linguistics and literary criticism — the translation of the poetic heritage of Lesya Ukrainkа by M. Komissarovа. Proposed in the article approaches to the translation of works that reflect the cultural and artistic features of the creative manner of the poetess, can be used in the reproduction of artistic means of other poets and writers. The relevance of the article is that the issues of translation transformations, with the help of which it is possible to make the transition from original units to translation units, have recently attracted the attention of domestic, foreign literary critics and translators. Translational transformations can not do without language units that have both a content plan and an expression plan, are of a formal and semantic character, transforming both the form and the meaning of the original units. The aim of the article is to present the cultural and artistic features of L. Ukrainkа’s creativity and determine the level of preservation of the author’s concept in the translation of her poetry, the reproduction of artistic and visual means, intramontext connections and imagery. The object of the study is the poetry of Lesya Ukrainka. The subject of the analysis is the peculiarities of translating Lesya Ukrainka’s poetic works into Russian.